Successful control of Echinococcosis in Argentina and Chile through a One Health approach, including vaccination of the sheep intermediate host - Thelma Veronica Poggio; Tomas Chacon; Edmundo Larrieu (Parasitology)
Cystic echinococcosis control in South American countries requires a comprehensive integrative ‘One Health’ approach. While insular nations have seen successful in their elimination programmes, South American countries face persistent challenges in hostile environments, with Echinococcus granulosus s.l., posing a significant public health concern. Vaccination of intermediate hosts has demonstrated the efficacy of the EG95 vaccine in reducing transmission rates. For example, since 2009, Rio Negro Province in Argentina has added, with marked success, the EG95 vaccine to the control programme, supplementing dog deworming. The Aysen Region of Chile has also reported encouraging preliminary results in reducing cyst prevalence in vaccinated sheep after 3 years of vaccination. The challenges in aligning control strategies with socio-cultural factors, especially in indigenous communities, underlines the need for context-specific strategies. The Rio Negro programme demonstrated commendable compliance, underlining the importance of community engagement in achieving lasting success. The most promising strategies for effective echinococcosis control involved dog deworming and the routine vaccination of sheep and/or goats, underscoring the importance of sustained implementation until all grazing animals have been replaced. For lasting success, these interventions need to be combined with a robust surveillance system.